Writing the early Medieval West: studies in honour of Rosamond McKitterick - Screen, Elina ca. 20./21. Jh.; West, Charles; McKitterick, Rosamond (Cambridge University Press, 2018)
"This volume took its current form as the result of conversations between Marios Costambeys, Matthew Innes, Elina Screen and Charles West at the Leeds International Medieval Congress in July 2015, and reflects the general desire of Rosamond McKitterick's students to mark her retirement in September 2016. "--